If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(3x-5)=2(x-52)-41
We move all terms to the left:
-5(3x-5)-(2(x-52)-41)=0
We multiply parentheses
-15x-(2(x-52)-41)+25=0
We calculate terms in parentheses: -(2(x-52)-41), so:We get rid of parentheses
2(x-52)-41
We multiply parentheses
2x-104-41
We add all the numbers together, and all the variables
2x-145
Back to the equation:
-(2x-145)
-15x-2x+145+25=0
We add all the numbers together, and all the variables
-17x+170=0
We move all terms containing x to the left, all other terms to the right
-17x=-170
x=-170/-17
x=+10
| x√3=4 | | y-35=52 | | −13(12a+18)=5(a−3) | | Y=16x^2-8x-24 | | 8d+6=38 | | 7f+17=8f-13+12 | | 32=3x-8 | | m-37=16 | | 29=−32r+17 | | 8x–12=-4 | | 2a2-14a-21=0 | | 3f-12+5f+2=3f-5 | | B=30.00-0.10x | | 2.4r+5.3=7.7 | | 3x-45=-21 | | 20+12m=-20+14m | | 2y-3+y=24 | | y+-13=-15 | | 8x+5=2x-16 | | 2(4x-1)=2(3x+1) | | 1.2x-2.5x=0.6x-0.7x= | | 4•z=35 | | 23c/4+2,c=10 | | 20r+-4r=16 | | f+54=79 | | x2+14=158 | | 15=x/4+6 | | 2(4x+6)=12x+1-4x+11 | | 7x-3=5x+-5 | | 55-5x=4(7-x) | | 45=g-20 | | x3+15=2 |